Application of Singing Activities to Stimulate Children's Vocabulary Acquisition - Simatupang, Nurhenti; Widayati, Sri; Adhe, Kartika Rinakit; Sholihah, Sefy Amaliatus (Universitas Nahdlatul Ulama Surabaya, 2022)
This study was motivated by ability acquisition children 's vocabulary in age 4-5 years is somewhat low, so that will impact negative in communicate with the surrounding environment. This research conducted to see children 's vocabulary acquisition at Kurnia Putra Kindergarten. This study this study used action class action research approach. Subject in study this that is child K1 (or TK A) which consists of 16 children. method data collection used is observation participatory. Data analysis techniques using statistics descriptive. Research results this is activity sing could stimulate acquisition children 's vocabulary age early at Kurnia Putra Kindergarten. the thing could be seen from acquisition child 's vocabulary in cycle I day first average category not enough as much as 87.5% and on the day second no there is category less. Cycle II days first average category not enough as much as 75% and on the day second already no there is category less. This also happened in the other 3 cycles.